The contagious impact of playing violent video games on aggression: Longitudinal evidence. Issue 6 (13th August 2019) - Greitemeyer, Tobias
Abstract: Meta‐analyses have shown that violent video game play increases aggression in the player. The present research suggests that violent video game play also affects individuals with whom the player is connected. A longitudinal study ( N  = 980) asked participants to report on their amount of violent video game play and level of aggression as well as how they perceive their friends and examined the association between the participant's aggression and their friends' amount of violent video game play. As hypothesized, friends' amount of violent video game play at Time 1 was associated with the participant's aggression at Time 2 even when controlling for the impact of the participant's aggression at Time 1. Mediation analyses showed that friends' aggression at Time 1 accounted for the impact of friends' amount of violent video game play at Time 1 on the participant's aggression at Time 2. These findings suggest that increased aggression in video game players has an impact on the player's social network.